The Effect of Personality Types on Blood Pressure in Female Patients Over 17 Years of Age - Bunga Fardah Nahdiyah Achmada; Dian Mutiasari; Abi Bakring Balyas; Lia Sasmithae; Helena Jelita (Jurnal Kedokteran Brawijaya, 2023)
Hypertension is non-communicable and one of the main sources of premature death in the world, but the cause of this disease generally is still unknown. It is important to note that personality types are included among the suspected influencing factors due to being related to controlling behavior, emotions, and stress. According to Hippocrates-Galenus, they are divided into sanguine, melancholy, choleric, and phlegmatic. Therefore, this research aimed to determine respondents' characteristics, differences in blood pressure (BP) between personality types, and the effect of personality types on BP. The design employed was descriptive-analytic with a cross-sectional approach, and the sample used was 56 respondents, selected by purposive sampling technique. The data on personality types were collected by filling out a questionnaire, while BP data were obtained through BP measurement with a digital tensimeter, and the analysis was conducted with Fisher's Exact, Kruskal-Wallis, and one-way ANOVA tests. The results showed that most respondents, i.e. 62.5% were aged 17-29 years, 20% had BMI ≥27 or Obesity, 10.7% had SBP/DBP=140-149/90-99 or hypertension stage 1, 37.5% were married, 26.8% had birth control history, alcohol consumption history =0%, smoking history =1.8%, 35.7% had phlegmatic personality type, and 10.7% suffered hypertension. The results showed that there was a significant difference between personality types and systolic and diastolic blood pressure, respectively p=0,03 and 0,045. There is no effect of each personality type on blood pressure (p>0,05). In conclusion, despite the different SBP and DBP values of personality types, no effect is created on BP.